Immediate Postpartum LARC Placement May Decrease the Risk of Short-Interval Pregnancy [3E]. (May 2018) - Higgins, Stephanie; Morosky, Christopher; Nelson, Amy
Abstract : INTRODUCTION: Short interval pregnancies are associated with an increased incidence of preterm birth, low birth weight, and small for gestational age infants. LARC devices have been shown to be safe and effective in helping women achieve an optimal inter-pregnancy interval, however those studies did not evaluate LARC placed in the immediate postpartum time period. METHODS: This is a retrospective cohort study of clinic patients who delivered at Hartford Hospital and requested immediate postpartum LARC. LARC devices were supplied by periodic shipments from the Ryan program. Near the end of shipment periods, there were often insufficient devices to meet demand. This led to a pseudo-random intervention in which some patients received their requested LARC device immediately postpartum and others were given a temporary method and asked to follow-up for outpatient LARC placement. The primary outcome was the percentage of patients in each group who experienced a short interval pregnancy RESULTS: 345 women qualified for study inclusion. 264 of those women received immediate postpartum LARC (76.5%). The overall number of short interval pregnancies was 39 (11.3%). Among women who received LARC, the percentage of short interval pregnancy was 9.8%. Among women who did not receive LARC, the percentage was 16.0%. Chi-squared comparison resulted in P=0.12 CONCLUSION: Due to a lower than expected overall incidence of short interval pregnancy, this study was underpowered to detect its primary outcome. This study may serve as a useful pilot study to aid future prospective studies examining the effect of immediate postpartum LARC placement on short interval pregnancy.